[Image 45] - Smith, Captain Sir William [?ob. 1732] (My University, 1804)
Captain Sir William Smith was in the Royal Engineers.
Original drawings and paintings of Ireland and Scotland, vol 1
View of Lough Swilly as seen from rocks near to [indecipherable] Point looking the way of Knochallaw and Dunree Forts or Batteries and down to Fannat Point drawn by Sir Wm Smith in 1804.
Keywords: Lough Swilly; Knochallaw; Fannat Point; Dunree; Fortification; Architectural drawings; Ireland -- Antiquities -- Pictorial works; Donegal (Ireland : County) -- Pictorial works; Inishowen Peninsula (Ireland) -- Pictorial works; Landscapes (Representations) 1800-1810